A Study on Prevention of Binder Elution to Improve Lifespan of PCD Tools and on Improvement of Bond Strength of Vacuum Brazing - Kwon, Sun-Pil; Jung, Byoung-Jo (International Journal of Engineering and Technology, 2018)
Background/Objectives: Process improvement of vacuum brazing and WEDM(Wire electric discharge machining) for improvement of lifespan of PCD(Polycrystalline diamond) tools.Methods/Statistical analysis: Comparison of the binder elution level under the exposure level of electrolyte in WEDM process for shape machining of PCD plate and measurement of the deflective strength of binding section and melting level of filler metal under vacuum brazing conditions.Findings: The level of binder elution under the exposure level of electrolyte in WEDM process for shape machining of PCD plate was compared and analyzed and the data were acquired through the deflective strength test of binding section under the temperature of vacuum brazing. The binder elution of over 70% was confirmed after precipitation of PCD plate into electrolyte for about 10 minutes. With respect to vacuum brazing process, the deflective strength test of PCD binding section after completion of brazing under the maximum heating temperature of 690â„ƒ had the outcome of 430[N/ãŽŸ].Improvements/Applications: The binder elution level under the exposure level of electrolyte of PCD plate was confirmed and through the setting of proper temperature on filler metal in vacuum brazing, the improvement of deflective strength of binding section was confirmed. It may be applied to manufacturing processes of various rotating tools like drill, end mill, cutting tool, etc.Â Â